FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL - Augustine, Mega; Ekadjaja, Agustin (Jurnal Paradigma Akuntansi, 2025)
The purpose of this study was to determine the effect of profitability, liquidity, firm size and asset structure on capital structure registered in mainboard primary consumer sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 Period. This study used 44 sample and 132 data from primary consumer primary companies which were selected using a purposive sampling method. The data of research were inputted and processed using Eviews 12 program. The result of research shows that profitability do not affect capital structure, liquidity and asset structure has a negative effect on capital structure, firm size has a positive effect on capital structure.